Adakah Perbedaan Kinerja Keuangan Perusahaan Farmasi Sebelum dan Selama Covid-19? - Annisa Lukman A. Gaffar; Rabihatun; La Ode Sumail (Jurnal Ekonomi, 2022)
The purpose of this research is to investigate whether there are significant differences in financial performance before Covid-19 and during Covid-19 in pharmaceutical companies listed on the IDX. The sample of this study was 9 companies and all of the population were sampled so that this study used the saturated sample technique. The analytical method used is a comparative test with a Paired T-test approach. The results of the study that ROE had a significant difference between before and during Covid-19 also had an impact on stock prices. Furthermore, the DPR has a significant difference between before and during Covid-19 so that it has an impact on stock prices. And lastly, PER has a significant difference between before and during Covid-19 which also has an impact on stock prices.